Implementation of the Simple Additive Weighting (SAW) Method for Supplier Selection - Muhyidin, Yusuf; Iman Hermanto, Teguh; Raymond Ramadhan, Yudhi; Irmayanti, Dede; Angga Permana, Muhammad (RISTEC : Research in Information Systems and Technology, 2024)
Supplier selection is a critical part of purchasing activities in a company because it has an impact on the quality and availability of raw materials, production cost efficiency and the smooth circulation of company finances. Determining suppliers based on certain criteria can be supported by a decision support system (DSS). The method used is the Simple Additive Weighting (SAW) method. The criteria used in selecting suppliers are speed of delivery, discount level, service, quality of goods and payment tempo. The final result obtained from the calculation process is a ranking table which shows the assessment of each supplier using the weight criteria determined by the company and recommends the supplier with the highest score as the best supplier. By implementing a decision support system using the Simple Additive Weighting (SAW) method, it can help companies determine and select suppliers who are able to provide good products. Keywords : Simple Additive Weighting Method; selection of supplier